1988
DOI: 10.1002/eji.1830181202
|View full text |Cite
|
Sign up to set email alerts
|

Activation of rat complement by soluble and insoluble rat IgA immune complexes

Abstract: The ability of rat monoclonal IgA, specific for 2,4-dinitrophenyl (DNA), to activate the complement (C) system of the rat was investigated using aggregated IgA or IgA immune complexes (IC). IgA was coated onto a solid phase, and tested for its capacity to bind C3 upon incubation at 37 degrees C in normal rat serum (NRS) in the presence of Mg-EGTA. Binding of C3 was observed dependent on the dose of dimeric (d-), polymeric (p-) and secretory IgA tested. In contrast, little C3 fixation was observed in this syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…Differences between mutant and wild-type sera were evaluated by a t test. ‫,ء‬ p ϭ 0.015; ‫,ءء‬ p ϭ 0.001. differences have been previously reported for activation of the alternative pathway by rat and human IgA (16,26,29). In addition, polymeric IgA shows enhanced binding to the phagocytic IgA FcR CD89 (33) and to human mesangial cells (34).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Differences between mutant and wild-type sera were evaluated by a t test. ‫,ء‬ p ϭ 0.015; ‫,ءء‬ p ϭ 0.001. differences have been previously reported for activation of the alternative pathway by rat and human IgA (16,26,29). In addition, polymeric IgA shows enhanced binding to the phagocytic IgA FcR CD89 (33) and to human mesangial cells (34).…”
Section: Discussionmentioning
confidence: 65%
“…Complement activation is known to be predominantly a function of polymeric IgA (26). We tested the different molecular sizes of IgA for their ability to activate the lectin pathway.…”
Section: Iga Activates the Complement System Via The Lectin Pathwaymentioning
confidence: 99%
“…In vitro studies showed that IgA aggregates and IgA-containing immune complexes may induce complement activation through the alternative pathway [43, 44]. On the other hand, Imaiet al [45]demonstrated that soluble IgA or renal localized IgA complexes fail to activate C3 in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, we observed that SBP-pullulan con jugate could form a precipitin line with anti-SBP antibodies in agarose gel immunodiffusion, but the line was a so-called 'clear line' (fig. 4), indicating the strong hydrophilicity of the precipitin line [11,12], Since the environment in which the antigen-antibody reaction occurs, or the surface nature of the particles, is known to influence the initiation of complement activation [13][14][15][16], the ability to initiate complement activation of the IC formed with SBP-pullulan differs from that of the IC formed with native SBP. Comple ment activations via CP and AP are detected by several methods, for example, the complement con sumption test, detection of cleavage fragments or con version of some complement components [14,17,18].…”
Section: Discussionmentioning
confidence: 99%
“…4), indicating the strong hydrophilicity of the precipitin line [11,12], Since the environment in which the antigen-antibody reaction occurs, or the surface nature of the particles, is known to influence the initiation of complement activation [13][14][15][16], the ability to initiate complement activation of the IC formed with SBP-pullulan differs from that of the IC formed with native SBP. Comple ment activations via CP and AP are detected by several methods, for example, the complement con sumption test, detection of cleavage fragments or con version of some complement components [14,17,18]. In the present study, we showed that IC consisting of SBP-pullulan and anti-SBP IgG was incapable of ac tivating the complement system effectively via both CP and AP since: (1) in the presence of Mg2+ and Ca2+ ions, the IC formed with SBP-pullulan and rabbit anti-SBP did not consume guinea pig complement at all, whereas the IC with native SBP completely con sumed 5 U CH50/ml complement, and (2) in serum treated with IC consisting of SBP-pullulan, conver sion of the human C3 component and cleavage of hu man factor B were observed as little in control serums treated with anti-SBP IgG alone or SBP-pullulan con jugate alone.…”
Section: Discussionmentioning
confidence: 99%